Si x - 1/x = 4
x3 - 1/x3 = 5
Calcule x2 + 1/x2
Herminio:
Hay contradicción entre las dos primeras. No puede determinarse al tercera
Respuestas
Respuesta dada por:
15
Tienes lo siguiente:
![x^3- (\frac{1}{x})^3=(x- \frac{1}{x} ) (x^2+x( \frac{1}{x} )+( \frac{1}{x} )^2) \\ 5=(4)(x^2+1+( \frac{1}{x} )^2) \\ \frac{5}{4}=1+x^2+ \frac{1}{x^2} \\ \frac{5}{4}-1=x^2+ \frac{1}{x^2} \\ \\ \boxed{ \frac{1}{4}=x^2+ \frac{1}{x^2} } x^3- (\frac{1}{x})^3=(x- \frac{1}{x} ) (x^2+x( \frac{1}{x} )+( \frac{1}{x} )^2) \\ 5=(4)(x^2+1+( \frac{1}{x} )^2) \\ \frac{5}{4}=1+x^2+ \frac{1}{x^2} \\ \frac{5}{4}-1=x^2+ \frac{1}{x^2} \\ \\ \boxed{ \frac{1}{4}=x^2+ \frac{1}{x^2} }](https://tex.z-dn.net/?f=x%5E3-+%28%5Cfrac%7B1%7D%7Bx%7D%29%5E3%3D%28x-+%5Cfrac%7B1%7D%7Bx%7D+%29+%28x%5E2%2Bx%28+%5Cfrac%7B1%7D%7Bx%7D+%29%2B%28+%5Cfrac%7B1%7D%7Bx%7D+%29%5E2%29+%5C%5C+5%3D%284%29%28x%5E2%2B1%2B%28+%5Cfrac%7B1%7D%7Bx%7D+%29%5E2%29+%5C%5C++%5Cfrac%7B5%7D%7B4%7D%3D1%2Bx%5E2%2B+%5Cfrac%7B1%7D%7Bx%5E2%7D++%5C%5C++%5Cfrac%7B5%7D%7B4%7D-1%3Dx%5E2%2B+%5Cfrac%7B1%7D%7Bx%5E2%7D+++%5C%5C++%5C%5C+%5Cboxed%7B+%5Cfrac%7B1%7D%7B4%7D%3Dx%5E2%2B+%5Cfrac%7B1%7D%7Bx%5E2%7D++%7D)
Saludos!
Saludos!
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años